GRINDING WHEEL MONITORING SYSTEM (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
It has been hypothesized that the change in the micro and macro geometry of the grinding wheel can be determined by a non-contact way by supplying jet of air through the nozzle of a pneumatic-electric-contact converter to the surface of the tool during operation. To confirm this hypothesis an experiment was did on a surface grinding machine. Various samples were machined, that led to self-sharpening of the tool. Grinding wheel monitoring system was developed for the experiments. System includes a device that provides the setting of the necessary working gap between the nozzle and the controlled wheel. A justification is proposed for determining the frequency of grinding wheel grinding during operation by accurately accounting for changes in the state of its surface without stopping the machining process.